Cerebrospinal Fluid CXCL10 as a Candidate Surrogate Marker for HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis - Tamaki, Keiko; Sato, Tomoo; Tsugawa, Jun; Fujioka, Shinsuke; Yagishita, Naoko; Araya, Natsumi; Yamauchi, Junji; Coler-Reilly, Ariella L. G.; Nagasaka, Misako; Hasegawa, Yasuhiro; Yamano, Yoshihisa; Tsuboi, Yoshio (Frontiers in Microbiology, 2019)
Human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a debilitating, progressive disease without effective treatment; therefore, development of disease modifying therapy that improves long-term functional outcomes is an unmet need for patients. However, it is virtually impossible to consider this as a primary endpoint in clinical trials owing to the prolonged disease course. Therefore, development of surrogate markers that help predict the effectiveness of new interventions is essential. Currently, several candidate surrogate markers have been identified for HAM/TSP. Cerebrospinal fluid (CSF) C-X-C motif chemokine 10 (CXCL10) is involved in the pathogenesis of HAM/TSP and was shown to correlate with disease progression. However, it remains unclear whether changes in CSF CXCL10 levels are observed in response to treatment and whether these correlate with prognosis. Here we investigated several markers, including CSF CXCL10, in this respect. Data pertaining to patient characteristics and results of motor function evaluation and CSF examination of 13 HAM/TSP patients who received steroid treatment were retrospectively analyzed. Osame motor disability scores (OMDS), 10 m walking time, and CSF levels of CXCL10, neopterin, total protein, cell counts, and anti-HTLV-1 antibody titer were compared before and after steroid therapy. Levels of all CSF markers, with the exception of cell count, were significantly decreased after treatment. Nine of the 13 patients (69.2%) showed improvement in OMDS and were considered responders. Pre-treatment CSF levels of CXCL10 and anti-HTLV-1 antibody titer in responders were higher than those in non-responders (p = 0.020 and p = 0.045, respectively). Patients who continued low-dose oral prednisolone maintenance therapy after methylprednisolone pulse therapy showed sustained improvement in OMDS and CSF CXCL10 and neopterin levels lasting for at least 6 months. In contrast, OMDS and the CSF marker levels in patients who discontinued treatment returned to pre-treatment levels after 2–3 months. Our findings suggest that CSF CXCL10 may serve as a therapy-response and therapy-predictive marker for HAM/TSP. In addition, since decrease in CSF CXCL10 level was associated with good functional prognosis, CSF CXCL10 is a potential surrogate marker for treatment of HAM/TSP.